Treatment of coronary artery disease with a new-generation drug-coated balloon: final results of the Italian Elutax SV rEgistry-DCB-RISE. Issue 5 (May 2018) - Cortese, Bernardo; D'Ascenzo, Fabrizio; Fetiveau, Raffaela; Balian, Vruyr; Blengino, Simonetta; Fineschi, Massimo; Rogacka, Renata; Lettieri, Corrado; Pavei, Andrea; D'Amico, Maurizio; Poli, Arnaldo; Di Palma, Gaetano; et al.
Abstract : Aims: Drug-coated balloons (DCBs) are a recognized alternative to stents for the treatment of in-stent restenosis (ISR), and there is some initial clinical evidence about their efficacy for the treatment of small coronary vessels. Newer-generation DCBs were developed to overcome the reduced deliverability of the previous generation, also warranting a more effective drug delivery to vessel wall. However, the vast majority of new-generation DCBs still lack of reliability due to paucity of clinical data. Methods: Between 2012 and 2015, all patients treated with Elutax SV DCB (Aachen Resonance, Germany) at nine Italian centers were enrolled in this retrospective registry. Primary outcome was the occurrence of target-lesion revascularization (TLR) at the longest available follow-up. Secondary endpoints were procedural success and occurrence of device-oriented adverse cardiovascular events including cardiac death, target-vessel myocardial infarction, stroke, and TLR. A minimum 6-month clinical follow-up was required. Results: We enrolled 544 consecutive patients treated at 583 sites. Fifty-three per cent of the patients had ISR, and the rest native vessel coronary artery disease. Procedural success occurred in 97.5%. At the longest available clinical follow-up (average 13.3 ± 7.4 months), 5.9% of the patients suffered a TLR and 7.1% a device-oriented adverse cardiovascular event. We did not register cases of target-vessel abrupt occlusion. At multivariate analysis, severe calcification at the lesion site was the first determinant for the occurrence of TLR. Conclusion: This registry on the performance of a new-generation DCB shows an adequate profile of safety and efficacy at mid-term clinical follow-up.